Sigma Rectrix Systems (M) Sdn Bhd / Siti Nur Hanis Aliaa Mohamad - Mohamad, Siti Nur Hanis Aliaa (Faculty of Business and Management, 2023)
Sigma Rectrix Systems (M) Sdn Bhd especially in the area of System Consultancy, Maintenance and Support Training and project management. Sigma Rectrix Systems (M) Sdn Bhd was founded in the year 2003 with accumulated more than 30 years of manpower experience. They focus on ICT services, especially in the area of System Integration, Software Development, Consultancy, Maintenance, Support, Training, and project management. They are the founder of e-Community in Malaysia and have strong support and professional expertise nationwide. As a result-oriented based company, they believe with great knowledge will bring great ideas, creativity, and innovation to move the company ahead of their competitors. A part from Sigma’s technological expertise, their sole rational existence is based on a market-oriented focus; acknowledging the importance of customer whether an existing customer or new; they work hard and their dedication to keeping a long-term relationship with the customers is bar to none. Sigma business operation supported by reputable technological partners will help their customers make the right decision and investments